Preliminary theoretical study of the formation and growth of droplets in nucleating flows - Hasini H.; Yusoff Mohd.Z.; Shuaib N.H. (2023)
This paper describes the preliminary study for the prediction of the formation and growth of water droplets in wet stages of a steam turbine. Emphasis is given towards the determination of suitable methods of calculation of suspended droplets in superheated steam. The one dimensional calculation is applied to a duct where superheated steam is allowed to supercool instantaneously as it enters the duct. At the same instance the formation of droplet embryos begins and subsequently, if the surrounding condition permits, it will grow by collecting its surrounding molecules. This process continue for a limited range of time and stops when the supercooling drops, at which the droplets can no longer survives and begins to evaporate. The accumulation of water droplets increases the level of wetness inside the duct. This mechanism is extremely important in the design and operation of low pressure steam turbine, in particular for the prediction of wet region within the machine. 2010 American Institute of Physics.